2010
DOI: 10.1159/000269779
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective Effect of Telmisartan in Rats with Ischemia/Reperfusion Renal Injury

Abstract: We investigated the protective effect of telmisartan, an angiotensin II receptor antagonist, against ischemia/reperfusion renal injury in rats. Bilateral ischemia was induced by clamping both renal vascular pedicles for 45 min followed by reperfusion for 3 h. Untreated rats exposed to ischemia/reperfusion showed significant elevations in blood urea nitrogen and serum creatinine levels, renal tissue levels of malondialdehyde, tumor necrosis factor-α and nitric oxide, and caspase-3 activity. This was associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 89 publications
4
23
0
Order By: Relevance
“…The decrease in caspase-3 expression in response to the administration telmisartan demonstrates that it prevented nerve cells from injury by decreasing the apoptotic pathway. In line with our study, previous data reported that telmisartan significantly attenuated increases in caspase-3 activity in renal injury, suggesting that telmisartan, through its anti-inflammatory and antiapoptotic effects, can be considered a potential candidate to protect against traumatic injuries [37]. In addi-tion, neuroprotective effects of pioglitazone, a PPAR-γ ligand of telmisartan, were shown to be mediated by inhibition of postischemic inflammation, neuronal degeneration, and apoptosis; by protection of neurons against ischemic injury; and by promotion of neuronal regeneration [38].…”
Section: Discussionsupporting
confidence: 92%
“…The decrease in caspase-3 expression in response to the administration telmisartan demonstrates that it prevented nerve cells from injury by decreasing the apoptotic pathway. In line with our study, previous data reported that telmisartan significantly attenuated increases in caspase-3 activity in renal injury, suggesting that telmisartan, through its anti-inflammatory and antiapoptotic effects, can be considered a potential candidate to protect against traumatic injuries [37]. In addi-tion, neuroprotective effects of pioglitazone, a PPAR-γ ligand of telmisartan, were shown to be mediated by inhibition of postischemic inflammation, neuronal degeneration, and apoptosis; by protection of neurons against ischemic injury; and by promotion of neuronal regeneration [38].…”
Section: Discussionsupporting
confidence: 92%
“…Other investigators have reported that telmisartan also suppressed oxidative stress in doxorubicin-induced nephrotoxicity [18], ischemia/reperfusion injury [19], and streptozotocin-induced diabetic nephropathy [20]. However, little is known about the therapeutic potential of telmisartan in type 2 diabetic nephropathy associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms are not fully understood, one attractive possible mechanism is that telmisartan may have antioxidative stress effects. We and other investigators have reported that the renoprotective effects of telmisartan are at least partly mediated by reducing oxidative stress in a variety of animal models including unilateral ureteral obstruction [17], doxorubicin-induced nephrotoxicity [18], ischemia/reperfusion injury [19], and type 1 diabetic nephropathy [20]. To address whether telmisartan suppresses oxidative stress and prevents diabetic nephropathy, we administered telmisartan to db/db mice, a mouse model of type 2 diabetes and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Molecules and peptide were reported to have protective effect on renal function in I/R injury. [13][14][15] Mesenchymal stem cells and human hematopoietic stem/progenitor cells were used to treat rat renal I/R injury, which facilitates repairing of renal tissue. [16][17][18] It has been demonstrated that lysophosphatidic acid (LPA) may protect renal function by antiinflammatory, inhibiting expression of tumor necrosis factor, inflow of neutrophilic granulocyte, and activation of complement.…”
Section: Introductionmentioning
confidence: 99%